Tanks on the beaches : a Marine tanker in the Pacific war - Neiman, Robert M., 1918- (Texas A & M University military history series, 2003)
Robert M. Neiman was one of the rare USMC officers to serve in both Iwo Jima and Okinawa battles. In this book, Neiman and his co-author, Kenneth W. Estes, relay vivid accounts of fighting in the Pacific War, as well as Marine Corps service during the entire World War II period.